Undereducation and overeducation in the Australian labour market - Voon, Derby; Miller, Paul (Blackwell Publishing Asia, 2005)
This paper uses data from the 1996 Census of Population and Housing Household Sample File (HSF) to study the incidence of mismatch between workers’ educational attainments and the requirements of their jobs, and the earnings consequences of this mismatch. It also examines whether mismatch contributes to the explanation of the gender wage differential in the Australian labour market. It is found that approximately 15.8 per cent of men and 13.6 per cent of women are overeducated, whereas approximately 18.5 per cent ofwomen and 13.7 per cent of men are undereducated. Substantial earnings consequences are found to be associated with this mismatch, with surplus schooling yielding relatively low returns. The results suggest that mismatch does not account for the gender wage gap in the Australian labour market; rather the gender wage differential is entrenched in the fundamentals of pay determination.